2016
DOI: 10.1186/s12891-016-1302-6
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatment of 2-part surgical neck fractures of the proximal humerus (AO 11-A3) in the elderly: Cement augmented locking plate Philos™ vs. proximal humerus nail MultiLoc®

Abstract: BackgroundProximal humeral fractures are with an incidence of 4–5 % the third most common fractures in the elderly. In 20 % of humeral fractures there is an indication for surgical treatment according to the modified Neer-Criteria. A secondary varus dislocation of the head fragment and cutting-out are the most common complications of angle stable locking plates in AO11-A3 fractures of the elderly. One possibility to increase the stability of the screw-bone-interface is the cement augmentation of the screw tips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
6
1
4
Order By: Relevance
“…The multiple xation techniques described in literature indicate that the optimal treatment for displaced proximal humeral fractures continues to be controversial [7,8,11,19,20,21] FiberWire, a representative nonabsorbable suture made of multi-strand, long-chain, ultra-high molecular weight polyethylene (UHMWPE) demonstrated higher strength than the other conventional sutures as Barber et al reported; its superiority showed remarkable statistical signi cance in our study (P < 0.001) [27]. Moreover, the rupture pattern differed between FiberWire and the other suture materials.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple xation techniques described in literature indicate that the optimal treatment for displaced proximal humeral fractures continues to be controversial [7,8,11,19,20,21] FiberWire, a representative nonabsorbable suture made of multi-strand, long-chain, ultra-high molecular weight polyethylene (UHMWPE) demonstrated higher strength than the other conventional sutures as Barber et al reported; its superiority showed remarkable statistical signi cance in our study (P < 0.001) [27]. Moreover, the rupture pattern differed between FiberWire and the other suture materials.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple fixation techniques described in literature indicate that the optimal treatment for displaced proximal humeral fractures continues to be controversial [7,8,11,[19][20][21]. The preferred operation technique depends on fracture type, patient age, bone quality, and functional expectation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with locking intramedullary nails is more consistent with the principle of minimally invasive surgery [13,14]; however, this approach also has several disadvantages, such as the potential for screw displacement and iatrogenic rotator cuff tears [15,16]. The improved 3 rd generation locking intramedullary nails show better biomechanical advantages and a signi cantly reduced risk of rotator cuff tear because the nail entry point is in the muscle portion of the supraspinatus [17][18][19].…”
Section: Introductionmentioning
confidence: 99%